Transannular reactions of two non-parallel 1,3-butadiyne units: syntheses, structures and protonation reactions of 1-isopropyl-1-azacyclopentadeca-3,5,11,13-tetrayne and 1-isopropyl-1-azacyclohexadeca-3,5,12,14-tetrayne - Schmidt, Erik M.; Gleiter, Rolf; Rominger, Frank (European journal of organic chemistry, 2004)
The syntheses of 1-isopropyl-1-azacyclopentadeca-3,5,11,13-tetrayne (15a) and 1-isopropyl-1-azacyclohexadeca-3,5,12,14-tetrayne (15b) were accomplished in a stepwise approach. The key intermediates were 1,14-dibromotetradeca-2,4,10,12-tetrayne (14a) and 1,15-dibromopentadeca-2,4,11,13-tetrayne (14b). The ring closure to 15a and 15b was achieved by reaction with isopropylamine. X-ray investigations on single crystals of 15a and 15b revealed a non-parallel orientation of the 1,3-butadiyne units. The reaction of 15b with concd. HCl in ethanol yielded 5,12-dichloro-2-isopropyl-1,2,3,6,7,8,9,10-octahydrocyclonona[e]isoindole (16c) and 5-chloro-2-isopropyl-2,3,6,7,8,9,10,11-octahydrocyclonona[e]isoindol-12(1H)-one (17c). A mechanism for the reaction of 15b with HCl is proposed. The reaction of 15a with concd. HCl in ethanol gives 5-chloro-2-isopropyl-2,3,7,8,9,10-hexahydrocycloocta[e]isoindol-11(6H)-one (24c). (© Wiley-VCH Verlag GmbH & Co. KGaA, 69451 Weinheim, Germany, 2004)